Legitimate Expectations as an Object of Corporate Legal Relations - S. O. Slipchenko; Yu. M. Zhornokui (Bulletin of Kharkiv National University of Internal Affairs)
The authors have conducted the analysis of the legislation of Ukraine, the case law of Ukraine and the European Court of Human Rights, as well as doctrinal approaches to understanding legitimate expectations as objects of corporate legal relations. It has been concluded that the share (capital share), and in fact participation in the company, is an asset associated with the occurrence of favorable property consequences in the future, and has all the characteristics of legitimate expectations. Participation in a company has all the characteristics necessary for its potential monetary evaluation, because it is negative from its owner (does not have a personal, inseparable connection with the person to whom it belongs), and therefore is potentially viable.